A Monte Carlo method to solve for radiative effective thermal conductivity for particle beds of various solid fractions and emissivities. (July 2020) - Johnson, Evan; Tarı, İlker; Baker, Derek
Highlights: A Monte Carlo method is described to calculate radiative effective thermal conductivity in monodisperse groups of spheres. Resulting krad values given for various combinations of particle volume fractions and emissivities. Equation given for krad, valid for any particle volume fraction from 0.25 to 0.64 and emissivity from 0.3 to 1. Abstract: A method is described to find the effective thermal conductivity due to radiation ( krad ) for groups of particles at packed and less than packed states. Unlike most previous studies, the method does not rely on the assumption of a unit cell or absorption and scattering coefficients to derive krad . In this method, radiation is modeled with a 3D Monte Carlo ray tracing code, steady state particle temperatures are found with a particle-particle heat exchange simulation, and krad is found with a comparison to heat conduction in an isotropic solid of the same geometry. This leads to the dimensionless Exchange Factor ( FE ), allowing krad to be calculated at any temperature and particle radius. The key result is a model for FE over the entire range of emissivities from 0.3 to 1 and solid fractions from 0.25 to the fully packed state of 0.64. FE results are compared to previous models, with agreement shown in some cases but a large disagreement found for low solid fractions. The krad results are combined with the Zehner and Schlünder model for solid and fluid conduction, providing an equation for the full effective thermal conductivity.